Conditioning Effect of Inhalational Anesthetics on Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage. Issue 2 (28th August 2020) - Athiraman, Umeshkumar; Dhar, Rajat; Jayaraman, Keshav; Karanikolas, Menelaos; Helsten, Daniel; Yuan, Jane; Lele, Abhijit V; Rath, Girija Prasad; Tempelhoff, Rene; Roth, Steven; Zipfel, Gregory J
Abstract: BACKGROUND: Delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (SAH) has been identified as an independent predictor of poor outcome in numerous studies. OBJECTIVE: To investigate the potential protective role of inhalational anesthetics against angiographic vasospasm, DCI, and neurologic outcome in SAH patients. METHODS: After Institutional Review Board approval, data were collected retrospectively for SAH patients who received general anesthesia for aneurysm repair between January 1st, 2010 and May 31st, 2018. Primary outcomes were angiographic vasospasm, DCI, and neurologic outcome as measured by modified Rankin scale at hospital discharge. Univariate and logistic regression analysis were performed to identify independent predictors of these outcomes. RESULTS: The cohort included 390 SAH patients with an average age of 56 ± 15 (mean ± SD). Multivariate logistic regression analysis identified inhalational anesthetic only technique, Hunt-Hess grade, age, anterior circulation aneurysm and average intraoperative mean blood pressure as independent predictors of angiographic vasospasm. Inhalational anesthetic only technique and modified Fishers grade were identified as independent predictors of DCI. No impact on neurological outcome at time of discharge was noted. CONCLUSION: Our data provide additional evidence that inhalational anesthetic conditioning in SAH patients affords protection against angiographic vasospasm and new evidence that it exerts a protective effect against DCI. When coupled with similar results from preclinical studies, our data suggest further investigation into the impact of inhalational anesthetic conditioning on SAH patients, including elucidating the most effective dosing regimen, defining the therapeutic window, determining whether a similar protective effect against early brain injury, and on long-term neurological outcome exists.